2017
DOI: 10.3758/s13423-017-1271-2
|View full text |Cite
|
Sign up to set email alerts
|

Testing the validity of conflict drift-diffusion models for use in estimating cognitive processes: A parameter-recovery study

Abstract: Researchers and clinicians are interested in estimating individual differences in the ability to process conflicting information. Conflict processing is typically assessed by comparing behavioral measures like RTs or error rates from conflict tasks. However, these measures are hard to interpret because they can be influenced by additional processes like response caution or bias. This limitation can be circumvented by employing cognitive models to decompose behavioral data into components of underlying decision… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
177
3
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 126 publications
(213 citation statements)
references
References 58 publications
11
177
3
1
Order By: Relevance
“…Because of the low number of errors, only the median RT for incorrect responses was used in the model fitting. A recent simulation-recovery study on the SSP showed that this approach provides accurate estimation of all of the parameters with the exception of the spotlight width (sd a ) and shrinking rate (r d ) (White, Servant, and Logan 2018). The simulation study showed that these two parameters cannot be estimated independently because they trade off with each other: a wide spotlight that shrinks rapidly can produce similar interference as a narrow spotlight that shrinks slowly.…”
Section: Shrinking Spotlight Analysismentioning
confidence: 99%
See 4 more Smart Citations
“…Because of the low number of errors, only the median RT for incorrect responses was used in the model fitting. A recent simulation-recovery study on the SSP showed that this approach provides accurate estimation of all of the parameters with the exception of the spotlight width (sd a ) and shrinking rate (r d ) (White, Servant, and Logan 2018). The simulation study showed that these two parameters cannot be estimated independently because they trade off with each other: a wide spotlight that shrinks rapidly can produce similar interference as a narrow spotlight that shrinks slowly.…”
Section: Shrinking Spotlight Analysismentioning
confidence: 99%
“…Based on a recent simulation study that did not observe such correlations from synthetic data, we believe that these negative correlations stem from the participants and data rather than trade-offs in the model (see White, Servant, and Logan 2018). Note that the positive within-participant correlations were not guaranteed because the model was fitted separately to each condition; thus, the strong correlations across cueing conditions for each parameter suggest the model fitting captured meaningful trends in the data.…”
Section: Shrinking Spotlight Analysesmentioning
confidence: 99%
See 3 more Smart Citations